Political resistance in Sheep Village: The politics of metaphors and their pedagogical implications - Ka Hang Wong (Universitas Ahmad Dahlan, 2026)
This study presents a critical discourse analysis of the Sheep Village children's trilogy and examines its pedagogical potential for the language education of Hong Kong children living in exile. Drawing on metaphor analysis, the study analyses how recurring figures such as the sheep, wolves, shepherd, and village allegorically represent collective agency, totalitarian power, moral leadership, and communal belonging in the context of the 2019 Hong Kong protests. The findings show that the texts construct resistance not through individual heroism but through ethical awareness, shared responsibility, and the preservation of cultural memory, offering young readers a narrative framework for understanding injustice and political power. Building on these findings, the article proposes pedagogical principles adapted from Critical English for Academic Purposes (CEAP) to support the integration of literary texts into language education. It argues that metaphor-rich narratives such as Sheep Village can be used to develop linguistic competence, emotional literacy, and critical civic awareness among children in exile communities, positioning children’s literature as a bridge between language learning, identity formation, and sociopolitical consciousness in host societies.